1993
DOI: 10.1039/dt9930001577
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and variable-temperature nuclear magnetic resonance of bis(bipyridine)ruthenium complexes containing dihydrazone ligands

Abstract: A series of dihydrazone and substituted dihydrazone derivatives of biacetyl and of hydrazone and phenylhydrazone derivatives of 2-acetylpyridine bind to [Ru(bipy),CI,] to give [Ru(bipy),( L-L)] -[PF,], complexes {bipy = 2.2'-bipyridine; L-L = biacetyl di(pheny1hydrazone) 1 a, biacetyl di [methyl(phenyl) hydrazone] 1 b, biacetyl di(o-tolylhydrazone) 1 c, biacetyl di(dimethy1hydrazone) 1 d, biacetyl di hydrazone 18, biacetyl di( benzaldehyde azine) 1 f, 2-acetylpyridine phenylhydrazone lg, or 2-acetylpyridine hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…In each case, the H 3 to H 6 protons of each pyridyl ring show the normal coupling patterns, , and assignments were made on the basis of COSY spectra (an example is given in Figure for the species ΔΛ/ΛΔ-[(Me 2 bpy) 2 Ru(μ-mapy)Ru(bpy) 2 ] 4+ ) and selective 1 H-decoupling experiments. In the case where methyl-substituted pyridyl rings were present (Me 2 bpy and mapy), the chemical shift of the methyl singlet is provided in Table in place of the H 4 signal.…”
Section: Resultsmentioning
confidence: 99%
“…In each case, the H 3 to H 6 protons of each pyridyl ring show the normal coupling patterns, , and assignments were made on the basis of COSY spectra (an example is given in Figure for the species ΔΛ/ΛΔ-[(Me 2 bpy) 2 Ru(μ-mapy)Ru(bpy) 2 ] 4+ ) and selective 1 H-decoupling experiments. In the case where methyl-substituted pyridyl rings were present (Me 2 bpy and mapy), the chemical shift of the methyl singlet is provided in Table in place of the H 4 signal.…”
Section: Resultsmentioning
confidence: 99%
“…Proton-NMR spectra of the complexes measured in acetonitrile solution show that the PR 3 ligand can rotate around the Re-P bond on the time scale of the NMR measurements, at least above −90 • C, since only four kinds of bpy-protons were observed for all of the complexes. The finer detail of their chemical shifts in Table 3 provides some information on the relative conformation between the ligands, however, Vos and co-workers 55 have reported that, in proton-NMR spectra of some ruthenium(II) bpy complexes with p-p interaction between the bpy ligands and a phenyl ring bonded to another ligand, aromatic proton resonances are upfield-shifted because of shielding effects of the ring currents. A similar shielding effect of the aryl group(s) on the triarylphosphine ligand is apparent on the bpy-protons in 3 + -6 + (Dd = −0.14 to −0.34 ppm compared with 7 + -9 + ), but is much weaker in 10 + (Dd = −0.05 to −0.22 ppm compared with 7 + -9 + ).…”
Section: Electrochemical and Spectroscopic Properties In Solutionmentioning
confidence: 99%
“…For example, Slugovc and coworkers17 successfully synthesized a new series of cyclometalated iridium complexes (ppy) 2 Ir(Q) (Q = 8‐quinolinolate, 5‐formyl‐8‐quinolinolate, and 5‐nitro‐8‐quinolinolate), and they found that (ppy) 2 Ir(Q) (Q = 8‐quinolinolate) is not luminescent in aerated as well as in degassed solutions, but the complexes can emit in the orange to red region by adding formyl or nitryl groups at the 5‐position of the 8‐quinolinolate ligand. By investigating a series of Ru dihydrazone and substituted Ru dihydrazone derivatives, Bolger et al18 concluded that Ru complexes with two hydrazone moieties are not emissive, but the [Ru(bipy) 2 (L–L)][PF 6 ] 2 complexes with one hydrazone (bipy = 2,2′‐bipyridine; L–L = 2‐acetylpyridine phenylhydrazone, 2‐acetylpyridine hydrazone) have good emissive properties. Moreover, Thompson and coworkers19 investigated the absorption and emission spectra of (ppy) 2 Ir(acac) and (ppy) 2 Ir(dbm), and they found that (ppy) 2 Ir(acac) is a good candidate for OLEDs with a lifetime of 1.6 μs and a quantum efficiency of 0.34, but (ppy) 2 Ir(dbm) gives very weak phosphorescence with a quantum efficiency less than 0.01.…”
Section: Introductionmentioning
confidence: 99%